Reducing prejudice by enhancing the other rather than the self. Issue 6 (18th August 2022) - Legault, Lisa; Coleman, Deonna; Jurchak, Kayla; Scaltsas, Nefeli
ABSTRACT: Self-enhancement may exacerbate ingroup favoritism. What if, rather than self-enhancement, individuals focused on enhancing others? Could this reduce prejudice? Three studies tested the impact of self-enhancement versus 'other-enhancement' on prejudice. In Study 1 (N=95), a repeated measures design showed that participants demonstrated less implicit bias after reflecting on another person's positive traits relative to their own. In Study 2 (N=169), participants who reflected on an outgroup strength showed less racism than those who reflected on an ingroup strength and those in a comparison condition. In Study 3 (N=380), other-enhancement negatively linked to racism and sexism, whereas self-enhancement did not. Additionally, Study 3 examined an antecedent of other-enhancement – humility. We discuss the importance of enhancing others in reducing prejudice.